Bidirectional Cavapulmonary Anastomosis as a Stage of Hemodynamic Correction of Hypoplastic Right Heart Syndrome - Elnur Imanov; Ivan V. Dziuryi; Iaroslav P. Truba; Iryna A. Perepeka; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2024)
Hypoplastic right heart syndrome (HRHS) is a rare cyanotic congenital heart disease with a wide spectrum of cardiac anomalies characterized by underdevelopment of the right heart. Survival and type of surgery in these patients directly correlate with structural anatomy and circulatory physiology.The aim. To evaluate perioperative characteristics in patients with HRHS, immediate and long-term results after bidirectional cavapulmonary anastomosis.Materials and methods. In the period from 1996 to 2022, 80 patients with HRHS underwent hemodynamic correction at the National Amosov Institute of Cardiovascular Surgery. All the patients were divided into three age groups: group I (n = 18) with patients who underwent hemodynamic correction under the age of 1 year, group II (n = 33) including patients who underwent surgery between the ages of 12 and 36 months, and group III (n = 29) comprised of those operated at the age older than 3 years.Results. In the early postoperative period, 5 (6%) deaths were reported among the patients of three groups: 3 in group I and 2 in group III. There were no deaths among patients of the group II. Median durations of mechanical ventilation, total exudation, hourly and total sympathomimetic support, hospital stay were significantly lower in group II in contrast to the comparison groups. An uncomplicated course of the early postoperative period was observed in 59 (74%) patients.Conclusions. In patients with HRHS, the determination of treatment tactics requires a careful approach, especially in newborns and infants. The implementation of hemodynamic correction shows significantly better results in early childhood.